2009
DOI: 10.1111/j.1460-9592.2009.03192.x
|View full text |Cite
|
Sign up to set email alerts
|

Second‐hand smoking and carboxyhemoglobin levels in children: a prospective observational study

Abstract: This study revealed interesting trends of COHb levels in children presenting for anesthesia and surgery. However, the COHb levels measured in our patients were close to the error margin of the device used in our study. An expected improvement in measurement technology may allow screening children for potential pulmonary perioperative risk factors in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 11 publications
1
10
0
Order By: Relevance
“…Our findings suggest that adolescent smokers and young children may become more susceptible to allergic sensitisation and ensuing asthma development, due to (short) cigarette smoke inhalation. In our opinion, these results can be extrapolated to humans, since our murine cigarette smoke exposure protocol reaches carboxyhaemoglobin (COHb) levels comparable to those in human smokers [28,29] and since COHb levels in young children (aged 1-2 years) exposed to parental smoke are similar to those measured in adult smokers [30].…”
Section: Discussionsupporting
confidence: 52%
“…Our findings suggest that adolescent smokers and young children may become more susceptible to allergic sensitisation and ensuing asthma development, due to (short) cigarette smoke inhalation. In our opinion, these results can be extrapolated to humans, since our murine cigarette smoke exposure protocol reaches carboxyhaemoglobin (COHb) levels comparable to those in human smokers [28,29] and since COHb levels in young children (aged 1-2 years) exposed to parental smoke are similar to those measured in adult smokers [30].…”
Section: Discussionsupporting
confidence: 52%
“…Although COHgb levels were not reported, carbon monoxide levels in the chambers [150–402 parts per million (PPM)] were 40–400% higher than the level needed to induce COHgb saturation of 10.5% (Harris et al, 2010). These are especially high compared with the values in non-smokers exposed to second-hand smoke (5.9 ng/ml of serum nicotine; Pacifici et al, 1995) and carbon monoxide levels of 5–20 PPM (Office of Technology Assessment, 1986), leading to COHgb levels of 4.43% (Yee et al, 2010). In addition to nicotine, tobacco smoke contains at least 4,000 additional substances, many of which are toxic or psychoactive, further complicating data interpretation.…”
Section: Animal Models Of Nicotine Abuse and Dependencementioning
confidence: 92%
“…It is thought that CO value measured in expirium air and COHb value measured simultaneously in blood gases are indicators of CO production namely cigarette consumption (3,4). In the study performed by Deveci et al (5) in which end-expiratory CO values were compared between non-smokers, active smokers and passive smokers, the values were found to be 3.61±2.15 ppm, 17.13±8.5 ppm and 5.2±3.38 ppm, respectively.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, it has been found that the rates of airway hyperreactivity and asthma are high in these children. All these can increase the risk of respiratory complications in the post-operative period especially in children who will undergo general anesthesia (2,3).…”
Section: Introductionmentioning
confidence: 99%